A comparison of anesthetic protective barriers for the management of COVID‐19 pediatric patients. Issue 3 (23rd December 2020) - Lee‐Archer, Paul; Boyd, Daniel; Du, Trung; Elliott, Robert; Graydon, Cameron; Paterson, Neil; Morawska, Lidia
Abstract: Background: Barrier techniques, such as plastic sheets or intubation boxes, are purported to offer additional protection for healthcare workers. Aims: To assess the functionality, perceived safety, droplet protection, and aerosol protection of several barrier techniques. Methods: Firstly, a simulation study with 12 different laryngoscopists was conducted to assess the time taken to perform an intubation (via direct laryngoscopy, via video laryngoscopy, and via a bougie) with four different barrier techniques (personal protective equipment only, a plastic sheet, a tented plastic sheet, and an intubation box). Secondly, a cough at the time of intubation was simulated using ultraviolet dye to assess the spread of droplets; and thirdly, smoke was used to assess the spread of aerosols. Results: Intubation time using the box was noninferior to using no barrier. Based on subjective ratings by the laryngoscopists, the most functional technique was no barrier followed by the intubation box, then the tented sheet, and then the plastic sheet. The technique that conferred the highest feeling of safety to the laryngoscopists was the intubation box, followed by the tented sheet, then no barrier, and then the plastic sheet. All the barriers prevented the ultraviolet dye contaminating the head and torso of the laryngoscopist. Smoke remained within the intubation box if plastics sheets were used to cover the openings and suction was ineffective at clearing it. With no barrier in place, smoke was effectively cleared away from the patient in a theater with laminar flow but tended to spread up toward the laryngoscopist in a room without laminar flow. Conclusions: A well‐designed intubation box is an effective barrier against droplets and is noninferior to no barrier in relation to intubation time. However, a box interferes with laminar flow in theaters with formal ventilation systems and may result in accumulation of aerosols if it is completely enclosed.